Is the Plant Bolboschoenus maritimus an Adequate Biomonitor for Trace Metal Contamination in Saltmarshes? A Field Study from the Óbidos Lagoon (Portugal) - Márcia S. S. Santos; Carmen A. Pedro; Susana M. F. Ferreira; Sílvia C. Gonçalves (Journal of Marine Science and Engineering, 2023)
Monitoring the negative impacts of trace metals is crucial to assess the health and stability of ecosystems. In salt marshes, halophyte plants were reported as possible bioaccumulators of these elements. The aim of this work was to explore the bioaccumulation potential of Bolboschoenus maritimus as a tool for monitoring the presence of metals in coastal environments. Bolboschoenus maritimus were collected from a brackish water lagoon, and the presence of the trace metals lead, cadmium, and nickel were seasonally evaluated in distinct parts of the plants, and in water and sediment samples. Lead was the trace metal with the highest concentration detected in water and sediments of the sampling site. The highest lead concentrations in B. maritimus were recorded in the spring season. The transport index indicated an accumulation of lead in the leaves of around 70% in the spring of 2009. Cadmium in leaves in spring and summer of 2009 reached values above 5 mg Cd. kg−1. Nickel was not detected in most samples collected. Bolboschoenus maritimus was considered an adequate biomonitor for lead and cadmium, since it bioaccumulates both metals with seasonally distinct results, as the bioaccumulation factor results indicated.